Research on the Development Strategy of Cultural and Creative Parks: A Case Study of Hongmei Park in Tiexi District, Shenyang - Yin Ruijia (SHS Web of Conferences)
In recent years, many regions have been vigorously promoting the development of cultural industry, and many cultural and creative parks continue to appear in people's vision. Industrial cultural and creative parks, as an important carrier of urban renewal and industrial heritage revitalization, provide a new growth point for the regional economy. Shenyang, as one of the important old industrial cities in the three northeastern provinces, has left a rich industrial heritage. With the rapid progress of science and technology and the steady development of society, many of the previous old factories in Tiexi District have been gradually eliminated. This paper takes Hongmei Cultural and Creative Park in Tiexi District of Shenyang as the research object to explore the development strategy of industrial cultural and creative park. From the excavation of historical value, the reshaping of urban memory points, the absorption of creative talents, the optimization of publicity channels and other aspects of the analysis, to find out the existing problems, and put forward the corresponding recommendations, aiming to provide a reference for the development of other industrial cultural and creative parks, to promote the protection and reuse of industrial heritage, and to promote the inheritance and development of urban culture.